Akibat Hukum Perjanjian Lisensi Terhadap Pihak Ketiga - I Kadek Bayu Surya Diana; I Nyoman Putu Budiartha; Ida Ayu Putu Widiati (Fakultas Hukum Universitas Warmadewa, 2019)
The licensing agreement means an agreement that functions as a group to regulate the legal ties between licensors and licensees. The license agreement must be registered by the minister in the general list of Copyright License agreements. However, what is a problem is whether the license agreement made by a special group is able to bind a third party if the copyright has not been registered based on the arrangement of procedures for recording the license agreement. Based on this, other problems arose in this research, namely (1) How to regulate procedures for registration of broadcasting license agreements, and (2) What are the legal consequences of licensing agreements with third parties. Based on this, there is a vacuum of norms found in Article 83 paragraph (4) of Law Number 28 of 2014 concerning Copyright; based on this matter the author examines this research using normative methods. In writing the author uses the method of legislative approach and legal concept analysis approach. In the source of legal material in this study on primary, secondary and tertiary legal materials. Finally the legal material collection technique uses a card system. Legal material analysis techniques used are descriptive techniques, interpretive techniques, evaluative techniques, systemic techniques and argumentative techniques. In a licensing agreement there is a legal consequence of a licensing agreement with a third party where one of the parties violates or defaults where the licensing agreement is not recorded at the Directorate General of Intellectual Property Rights which only binds the parties to the agreement, namely the licensor and the licensee. A result that can occur from the existence of bad faith, or default by the parties, the agreement can be canceled or null and void by law. The legal settlement efforts in the misappropriation of this licensing agreement can be done by non-Litigation and litigation.